A novel disease-causing variant associated with a milder phenotype of AARS2-related leukodystrophy — A case report - Joana Fernandes; João Moura; João Tarrio; Jorge Oliveira; Ana Lopes; João Parente Freixo; Gonçalo Videira (Molecular Genetics and Metabolism Reports)
Background and objectives: Adult-onset leukodystrophies are a rare group of neurological disorders characterized by progressive degeneration of the cerebral white matter. One of these diseases is caused by biallelic pathogenic variants in the AARS2 gene. We describe a patient with late-onset AARS2-related leukoencephalopathy, a milder phenotype and a novel disease-causing variant. Methods: The patient was characterized during routine clinical practice. Results: A 40-year-old male was evaluated for chronic headaches. Six years before, he was hospitalized for a major depression with psychotic features. The first neurological examination was normal, except for a slow downbeat nystagmus. Brain MRI revealed significant hyperintensities in T2 and T2-FLAIR bilaterally in the frontal lobes, with periventricular and corpus callosum involvement, and without restricted diffusion. A multigene panel for leukodystrophies based on whole-exome sequencing identified two heterozygous variants in the AARS2 gene: one previously reported in the literature, already classified as pathogenic, NM_020745.4:c.595C > T (p.(Arg199Cys)), and one novel variant c.730G > A (p.(Val244Ile)), later reclassified as likely pathogenic. Nine years have passed since the first symptoms without clear clinical progression. Discussion: This case underlines that adult-onset leukodystrophy caused by variants in AARS2 may have a wide range of phenotypes and patterns of progression. The new variant c.730G > A (p.(Val244Ile)) herein described may induce a milder clinical picture and a less severe radiological pattern. Practical implications: Adult-onset leukoencephalopathies may present with milder clinical signs than what is generally perceived, and novel disease-causing variants are being identified.